1975
DOI: 10.1111/j.1432-1033.1975.tb03945.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA Genes in the Amoebal and Plasmodial Forms of the Slime Mould Physarum polycephalum

Abstract: 1. The degree of homology between ribosomal RNA isolated from microplasmodia and amoebae of the slime mould Physarum polycephalum has been determined by competitive hybridisation of the RNA from the two sources to homologous DNA in solution. The extent of competition was measured both by hybridisation to saturation and by following the kinetics of hybrid formation.In each case competition was found to be 100 %, indicating that the ribosomal RNAs from the two, quite different vegetative forms of the organism ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…One would expect to find only a low percentage of such molecules in purified rDNA since (a) it takes about 8 h (an entire mitotic cycle minus the first hour) to double the population of about 300 ribosomal genes [2, 13,23], or 150 rDNA molecules, and (b) a single molecule probably replicates in less than 30 min. The latter assumption is based on the known rate of fork displacement in higher eucaryotes, about 2 x lo6 g mol-l min-' [14] and on our preliminary experiments with density labeling, which showed that intact rDNA of hybrid density appeared in less than 30 min after placing a G-2 plasmodium in medium with BrdUrd.…”
Section: The Mechanism Of Replicationmentioning
confidence: 99%
“…One would expect to find only a low percentage of such molecules in purified rDNA since (a) it takes about 8 h (an entire mitotic cycle minus the first hour) to double the population of about 300 ribosomal genes [2, 13,23], or 150 rDNA molecules, and (b) a single molecule probably replicates in less than 30 min. The latter assumption is based on the known rate of fork displacement in higher eucaryotes, about 2 x lo6 g mol-l min-' [14] and on our preliminary experiments with density labeling, which showed that intact rDNA of hybrid density appeared in less than 30 min after placing a G-2 plasmodium in medium with BrdUrd.…”
Section: The Mechanism Of Replicationmentioning
confidence: 99%
“…polycephulum hybridises with the cytoplasmic rRNAs [33,14]; the figure is independent of ploidy [14] and there are about 300 genes for rRNA per haploid genome. The genes have been identified as a component of a 'heavy' nuclear satellite DNA, the replication of which is unusual in that it occurs throughout the mitotic cycle [32,33,38], with the possible exception of the first hour after mitosis [32].…”
Section: Fig 2 Synthesis Q F R R N a Dnring Tlw Mitotic Cycle In Stmentioning
confidence: 99%
“…The frozen preparations, which were stored in liquid N2 until required, were homogenised in deproteinisation medium and RNA isolated as described previously [14]. Fractions containing the 19-S and 2 6 4 rRNAs from sucrose density gradients were combined and the concentration of rRNA determined by measuring the absorbance at 258 nm (A;:,, = 221).…”
Section: Preparation Of Rrnamentioning
confidence: 99%
“…The difference in chromosome number between S. cerevisiae (17) and K. marxianus (9) should not account for this difference, since Neurospora crassa with 7 chromosomes has 100 cistrons per nucleus (Chattopadhyay et al, 1972). Furthermore, an increase in the level of ploidy does not lead to any increase in the number of cistrons per nucleus in Physarum polycephalum (Hall et al, 1975).…”
Section: Discussionmentioning
confidence: 99%